Nuclear energy: a case for fear-defying sustainability - Goldstein, Joshua S. (Henry Stewart Talks, 2023)
Nuclear energy, Carbon goals, Sweden, France, Public fears, Fossil fuels, China, Russia, Fukushima power plant, Chernobyl, Decarbonization, Public opinion, Government policy, Small modular reactor, Micro reactor, Mass production, Scalability